Refining cardiac resynchronization therapy: a comprehensive review on the role of advanced multimodality imaging - Stoiculescu, Flavia-Mihaela; Hădăreanu, Diana-Ruxandra; Hădăreanu, Călin-Dinu; Donoiu, Ionuț; Florescu, Cristina (Frontiers in Cardiovascular Medicine, 2024)
Cardiac resynchronization therapy (CRT) offers significant benefits in symptom alleviation, reduction of rehospitalization rates, and overall survival of patients with heart failure (HF) with reduced ejection fraction (rEF). However, despite its proven efficacy, precisely identifying suitable CRT candidates remains a challenge, with a notable proportion of patients experiencing non-response. Accordingly, many attempts have been made to enhance patient selection, and to identify the best imaging parameters to predict the response and survival after CRT implantation. This review article provides a comprehensive overview on the role of multi-modality cardiac imaging in selecting, optimizing, and predicting CRT response and outcomes in HFrEF patients, beginning with an exploration of dyssynchrony types and their impact on HF progression, and an emphasis on the utility of echocardiography in assessing cardiac dyssynchrony. Subsequently, the role of advanced techniques such as speckle tracking and three-dimensional echocardiography, as well as the visual assessment of apical rocking (ApRock) and septal flash (SF) are highlighted. Finally, cardiac magnetic resonance (CMR) scar data, and novel modalities like four-dimensional flow CMR, together with single-photon emission computed tomography offer additional insights, emerging as valuable predictors of CRT response, and potentially refining the identification of suitable CRT candidates.